Isavuconazole As Successful Salvage Therapy for Mucormycosis in Pediatric Patients. Issue 8 (August 2020) - Ashkenazi-Hoffnung, Liat; Bilavsky, Efraim; Levy, Itzhak; Grisaru, Galia; Sadot, Efraim; Ben-Ami, Ronen; Novikov, Anna; Fischer, Salvador; Nahum, Elhanan; Scheuerman, Oded
Abstract : Background: Mucormycosis is a rare but emerging life-threatening fungal disease with limited treatment options. Isavuconazole is a new triazole that has shown efficacy in adults for primary and salvage treatment of mucormycosis. However, data in children are scarce. Methods: The demographic and clinical data of pediatric patients with proven mucormycosis who were treated with isavuconazole in 2015 to 2019 at 2 centers were collected. Results: Four children of median age 10.5 years (range 7–14) met the study criteria. Three had underlying hematologic malignancies, and 1 had sustained major trauma. Isavuconazole was used as salvage therapy in all: in 3 patients for refractory disease, and in 1 after intolerance to another antifungal drug. Isavuconazole was administered alone or combined with other antifungal agents. Following treatment and surgical intervention, complete clinical, radiologic and mycologic responses were documented in all patients. A literature review identified 8 children with mucormycosis who were successfully treated with isavuconazole, as salvage therapy in the majority. Conclusion: Our limited experience supports the use of isavuconazole as salvage therapy in pediatric mucormycosis. Abstract : Supplemental Digital Content is available in the text.